"Killer coronary artery" and aortic valve stenosis: A tricky case. (November 2015) - Nader, Joseph; Labont, Béatris Alina; Houpe, David; Caus, Thierry
Anomalous origin of the left main coronary artery from the right coronary sinus is rarely diagnosed in elderly patients. We report such an anomaly in a 75-year-old lady presenting with chest pain and syncope. Preoperative screening revealed that her aortic valve was moderately stenotic. The patient underwent a successful unroofing procedure combined with aortic valve replacement. The outcome was uncomplicated and the patient remained asymptomatic at one year postoperatively.